2006
DOI: 10.1007/s00253-005-0259-4
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm development of the polyethylene-degrading bacterium Rhodococcus ruber

Abstract: We have recently isolated a biofilm-producing strain (C208) of Rhodococcus ruber that degraded polyethylene at a rate of 0.86% per week (r2=0.98). Strain C208 adheres to polyethylene immediately upon exposure to the polyolefin. This initial biofilm differentiates (in a stepwise process that lasts about 20 h) into cell-aggregation-forming microcolonies. Further organization yields "mushroom-like" three-dimensional structures on the mature biofilm. The ratio between the population densities of the biofilm and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
150
3
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 314 publications
(163 citation statements)
references
References 14 publications
5
150
3
5
Order By: Relevance
“…Several previous studies have reported on biodegradation of polythene by bacterial [2,11] and fungal species [2,4,13] It has been reported that Pseudomonas spp. degrade polythene bags made of LDPE in natural as well as artificial environment.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have reported on biodegradation of polythene by bacterial [2,11] and fungal species [2,4,13] It has been reported that Pseudomonas spp. degrade polythene bags made of LDPE in natural as well as artificial environment.…”
Section: Introductionmentioning
confidence: 99%
“…One is the search for microorganisms for the degradation of polymers. [4][5][6] However, since the presence of polymers in nature's evolution is very short, it is very hard to nd new organisms capable of degrading synthetic polymers in nature. Another approach is the preparation of environmentally friendly polymers, 7-9 which can be easily degraded by microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…[19] Polyethylene Brevibacillus borstelensis [36] Rhodococcus rubber [37] Penicillium simplicissimum YK [9] Brevibacillus borstelen [38] Penicillium frequentans Bacillus mycoides [10] Aspergillus niger Penicillium pinophilium [11] Penicillium pinophilium Aspergillus niger Cliocladium virens Penicillium chrysosporium [12] Bacillus sphericus Bacillus cereus [13] Streptomyces spp. • 생물적 요인: 세포 외 효소분비, 소수성 표면으로의 부착 정도, 바이오 계면활성제 등.…”
Section: 미생물에 의해 이루어진다 플라스틱으로 사용되는 다양한 고분자들은 분자량이 크기 때문에 용해도가 낮고 미생unclassified